2018
DOI: 10.1186/s12885-018-4055-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated systemic levels of the matrix metalloproteinase inhibitor TIMP-1 correlate with clinical markers of cachexia in patients with chronic pancreatitis and pancreatic cancer

Abstract: BackgroundTissue inhibitor of metalloproteinases-1 (TIMP-1) is a candidate diagnostic and prognostic biomarker for pancreatic ductal adenocarcinoma (PDAC). Here, we determined the possible association of systemic TIMP-1 levels with cachexia and jaundice, two common PDAC-associated conditions.MethodsPlasma TIMP-1 was measured by ELISA in patients diagnosed with PDAC (n = 36) and chronic pancreatitis (CP) (n = 25). Patients without pancreatic pathologies and known malignancies of other origin served as controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…Protein network analysis indicated that these proteins were interconnected with known PDAC pathways and oncogenes, including KRAS (GTPase KRas), SMAD4 (Mothers against decapentaplegic homolog 4), CDKN2A (Cyclin-dependent kinase inhibitor 2A), MYC (Myc proto-oncogene protein), TP53 (Cellular tumor antigen p53), TNF (Tumor necrosis factor), TGFB1 (Transforming growth factor beta-1 proprotein) and EGF (epidermal growth factor) ( Figure S3). It is noteworthy that despite the relatively low blood concentration of TIMP1 (at low ng/mL level), this protein was included for further testing in this study, as its blood concentration has been previously associated with PDAC in multiple studies [8,12,13,23].…”
Section: Plasma Protein Candidates Associated With Early-stage Pdac Imentioning
confidence: 99%
See 1 more Smart Citation
“…Protein network analysis indicated that these proteins were interconnected with known PDAC pathways and oncogenes, including KRAS (GTPase KRas), SMAD4 (Mothers against decapentaplegic homolog 4), CDKN2A (Cyclin-dependent kinase inhibitor 2A), MYC (Myc proto-oncogene protein), TP53 (Cellular tumor antigen p53), TNF (Tumor necrosis factor), TGFB1 (Transforming growth factor beta-1 proprotein) and EGF (epidermal growth factor) ( Figure S3). It is noteworthy that despite the relatively low blood concentration of TIMP1 (at low ng/mL level), this protein was included for further testing in this study, as its blood concentration has been previously associated with PDAC in multiple studies [8,12,13,23].…”
Section: Plasma Protein Candidates Associated With Early-stage Pdac Imentioning
confidence: 99%
“…(Transforming growth factor beta-1 proprotein) and EGF (epidermal growth factor) ( Figure S3). It is noteworthy that despite the relatively low blood concentration of TIMP1 (at low ng/mL level), this protein was included for further testing in this study, as its blood concentration has been previously associated with PDAC in multiple studies [8,12,13,23].…”
Section: Plasma Protein Candidates Associated With Early-stage Pdac Imentioning
confidence: 99%
“…Similarly, addition of TIMP‐1 to CA19‐9, the currently used clinical marker for PDAC, may significantly improve PDAC detection (Capello et al, ). However, a few recent studies report that serum or plasma TIMP‐1 levels may be an indicator of PDAC‐associated cachexia or obstructive jaundice rather than a candidate marker for PDAC lesions (Jenkinson et al, ; Prokopchuk et al, ).…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 99%
“…Mroczko et al reported that the tissue inhibitor of metalloproteinase 1(TIMP‐1) is a potential marker of PC with AUC of 0.923, which is superior to CA 19‐9 (0.862), CEA (0.894) and matrix metalloproteinase‐9 (MMP‐9) (0.711). TIMP‐1 has also been found with elevated level in serum orplasma in PC pateints compared with healthy subjects and CP patients in other studies and is superior to MMP‐9 in the diagnosis of PC…”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 67%
“…Mroczko et al 38 reported that the tissue inhibitor of metalloproteinase 1(TIMP-1) is a potential marker of PC with AUC of 0.923, which is superior to CA 19-9 (0.862), CEA (0.894) and matrix metalloproteinase-9 (MMP-9) (0.711). TIMP-1 has also been found with elevated level in serum orplasma in PC pateints compared with healthy subjects and CP patients in other studies 39,40,42,48 and is superior to MMP-9 in the diagnosis of PC. 41 Urinary urokinase-type plasminogen activator receptor (uPAR)/ creatinine values are also reported as an accurate marker for PC diagnosis with 53.2% sensitivity and 93.6% specificity, which is significantly increased in patients with PC but is not correlated with the severity.…”
Section: Risk Factors Of Pcmentioning
confidence: 70%